Pyronaridine‐artesunate for treating uncomplicated Plasmodium falciparum malaria - Pryce, Joseph (Cochrane Database Syst Rev, 2019)
BACKGROUND: The World Health Organization (WHO) recommends artemisinin‐based combination therapies (ACTs) to treat uncomplicated Plasmodium falciparum (P falciparum) malaria. Concerns about artemisinin resistance have led to global initiatives to develop new partner drugs to protect artemisinin derivatives in ACT. Pyronaridine‐artesunate is a novel ACT. OBJECTIVES: To evaluate the efficacy of pyronaridine‐artesunate compared to alternative ACTs for treating people with uncomplicated P falciparum malaria, and to evaluate the safety of pyronaridine‐artesunate and other pyronaridine treatments compared to alternative treatments. SEARCH METHODS: We searched the Cochrane Infectious Diseases Group Specialized Register; Cochrane Central Register of Controlled Trials (CENTRAL), published in the Cochrane Library; MEDLINE; Embase; and LILACS. We also searched ClinicalTrials.gov, the WHO International Clinical Trials Registry Platform Search Portal, and the International Standard Randomized Controlled Trial Number (ISRCTN) registry for ongoing or recently completed trials. The date of the last search was 8 May 2018. SELECTION CRITERIA: Efficacy analysis: randomized controlled trials (RCTs) of pyronaridine‐artesunate for treating uncomplicated P falciparum malaria. Safety analysis: RCTs of pyronaridine‐artesunate or pyronaridine for treating P falciparum or P vivax malaria. DATA COLLECTION AND ANALYSIS: For this update, two review authors independently re‐extracted all data and assessed certainty of evidence. We meta‐analysed data to calculate risk ratios (RRs) for treatment failures between comparisons, and for safety outcomes between and across comparisons. MAIN RESULTS: We included 10 relevant studies. Seven studies were co‐funded by Shin Poong Pharmaceuticals which manufactures the drug. Three studies were funded by government agencies. For efficacy analysis we identified five RCTs with 5711 participants. This included 4465 participants from 13 sites in Africa, and 1246 participants from five sites in Asia. It included 541 children aged less than five years. For polymerase chain reaction (PCR)‐adjusted failures at day 28, pyronaridine‐artesunate may have fewer failures compared to artemether‐lumefantrine (RR 0.59, 95% confidence interval (CI) 0.26 to 1.31; 4 RCTs, 3068 participants, low‐certainty evidence), artesunate‐amodiaquine (RR 0.55, 95% CI 0.11 to 2.77; 1 RCT, 1245 participants, low‐certainty evidence), and mefloquine plus artesunate (RR 0.37, 95% CI 0.13 to 1.05; 1 RCT, 1117 participants, low‐certainty evidence). For unadjusted failures at day 28, pyronaridine‐artesunate may have fewer failures compared to artemether‐lumefantrine (RR 0.27, 95% CI 0.13 to 0.58; 4 RCTs, 3149 participants, low‐certainty evidence), and probably has fewer failures compared to artesunate‐amodiaquine (RR 0.49, 95% CI 0.30 to 0.81; 1 RCT, 1257 participants, moderate‐certainty evidence) and mefloquine plus artesunate (RR 0.36, 95% CI 0.17 to 0.78; 1 RCT, 1120 participants, moderate‐certainty evidence). For PCR‐adjusted failures at day 42, pyronaridine‐artesunate may make little or no difference compared to artemether‐lumefantrine (RR 0.86, 95% CI 0.49 to 1.51; 4 RCTs, 2575 participants, low‐certainty evidence) and artesunate‐amodiaquine (RR 0.98, 95% CI 0.20 to 4.83; 1 RCT, 1091 participants, low‐certainty evidence), but may have higher failures than mefloquine plus artesunate (RR 1.80, 95% CI 0.90 to 3.57; 1 RCT, 1037 participants, low‐certainty evidence). Overall, pyronaridine‐artesunate had a PCR‐adjusted treatment failure rate of less than 5%. For unadjusted failures at day 42, pyronaridine‐artesunate may have fewer failures compared to artemether‐lumefantrine (RR 0.61, 95% CI 0.46 to 0.82; 4 RCTs, 3080 participants, low‐certainty evidence), may make little or no difference compared to mefloquine plus artesunate (RR 0.84, 95% CI 0.54 to 1.31; 1 RCT, 1059 participants, low‐certainty evidence), and probably makes little or no difference compared to artesunate‐amodiaquine (RR 0.98, 95% CI 0.78 to 1.23; 1 RCT, 1235 participants, moderate‐certainty evidence). For the safety analysis of severe adverse events and liver function, we identified eight RCTs with 6614 participants comparing pyronaridine‐artesunate to other antimalarials, four of which were not in the previous version of this review. A further two RCTs, comparing pyronaridine alone to other treatments, contributed to the synthesis of all adverse events. Raised alanine aminotransferase (ALT) greater than five times the upper limit of normal (> 5 x ULN) is more frequent with pyronaridine‐artesunate compared to other antimalarials (RR 3.34, 95% CI 1.63 to 6.84; 8 RCTS, 6581 participants, high‐certainty evidence). There is probably little or no difference for raised bilirubin > 2.5 x ULN between pyronaridine‐artesunate and other antimalarials (RR 1.03, 95% CI 0.49 to 2.18; 7 RCTs, 6384 participants, moderate‐certainty evidence). There was one reported case in which raised ALT occurred with raised bilirubin, meeting criteria for moderate drug‐induced liver injury. No study reported severe drug‐induced liver injury. Electrocardiograph (ECG) abnormalities were less common with pyronaridine‐artesunate compared to other antimalarials. We identified no other safety concerns. AUTHORS' CONCLUSIONS: Pyronaridine‐artesunate was efficacious against uncomplicated P falciparum malaria, achieved a PCR‐adjusted treatment failure rate of less than 5% at days 28 and 42, and may be at least as good as, or better than other marketed ACTs. Pyronaridine‐artesunate increases the risk of episodes of raised ALT > 5 x ULN. This meets criteria for mild drug‐induced liver injury. On one instance this was linked to raised bilirubin, indicating moderate drug‐induced liver injury. No episodes of severe drug‐induced liver injury were reported. The findings of this review cannot fully inform a risk‐benefit assessment for an unselected population. Readers should remain aware of this uncertainty when considering use of pyronaridine‐artesunate in patients with known or suspected pre‐existing liver dysfunction, and when co‐administering with other medications which may cause liver dysfunction. 12 April 2019 Up to date All studies incorporated from most recent search All eligible published studies found in the last search (8 May, 2018) were included